Teachers' perspective on gratitude within classroom environment - Cedillo Berber, Leonardo (2015)
The present is a qualitative research on the topic of gratitude, specifically in classroom contexts. Its main purpose is to explore potential situations where gratitude is speculated to be present within classroom activities. The research took place in a primary school in the city of Jyväskylä, Finland. Two different groups of this school were videotaped during one of their lesson and the material was used in stimulated recall interviews. In the stimulated recall interview, teachers gave accounts about the different grateful moments and provided information about their thoughts and possible reasons why children were grateful. The main results from this investigation highlight seven different areas where gratitude presumably takes place according to teachers’ accounts, namely everyday routines, emotions, classroom and class tools, learning strategies, empathy, time and competence. Moreover, a complementary phenomenon named as evocative biography emerged from teacher’s accounts and the data. This provides information about the children´s background and reflects the interactive essence of gratitude. The study provides support and insight about the idea that gratitude in the school environment has meaning in its own right, thus deserving attention in order to provide suggestions on how to help students to identify, feel and express gratitude.